Solitary Plasmacytoma of the Mandible: Early Diagnosis and Surgical Management. Issue 5 (July 2019) - Rullo, Rosario; Scalzone, Paola; Laino, Luigi; Russo, Andrea; Festa, Vincenzo Maria; Fiorillo, Luca; Cicciù, Marco
Abstract : Abstract: Solitary plasmacytoma is an abnormal proliferation of B-lymphoid cells that involves a single bone. It mainly affects the axial skeleton; the jaw localization is a rare condition. The authors present a case of a 70-year-old female patient with a radiolucency of the angle of the mandible later diagnosed as solitary plasmacytoma.